Pelaksanaan Kompensasi Terhadap Pekerja Yang Di PHK (Studi Kasus Di Hotel X) - Amanda Istianah Mutiawati; Eka Saputra (Lembaga Pengembangan Kinerja Dosen, 2023)
Problems related to labor or labor are problems that often occur in developing countries, one of which is Indonesia. Termination of Employment (PHK) is something that is feared by workers due to economic conditions which have an impact on companies that have to go out of business and this results in unilateral layoffs by the company. One of the implementing regulations for the Job Creation Law that has been issued is Government Regulation Number 35 of 2021 concerning Work Agreements for Specific Periods, Outsourcing, Working Time, Work Relations and Rest Periods, and Termination of Employment (PHK). Article 15 states that employers are required to provide compensation money to workers or laborers whose employment relationship is based on a Specific Time Work Agreement (PKWT). Compensation money as referred to in Article 15 paragraph (1) PP Number 35 of 2021, is given to workers/laborers who have had continuous service for at least 1 (one) month. Compensation is everything that is received by workers, both physical and non-physical. The form of compensation given can be in the form of money or goods that are given directly or indirectly. Regulations regarding compensation are regulated in Law Number 13 of 2003 concerning Manpower and Government Regulation Number 35 of 2021 concerning Work Agreements for Specific Periods, Outsourcing, Working Time and Break Time and Termination of Employment. The compensation given by Hotel X to Mrs. S is in accordance with Article 16 of Government Regulation Number 35 of 2021 concerning Work Agreements for Specific Time, Outsourcing, Working Time and Break Time and Termination of Employment. Where Mrs. S demanded compensation from Hotel X with the calculation of the remaining salary withheld due to covid reasons, overtime pay, and leave money.